Moderate Hypothermia Improves Cardiac and Vascular Function in a Pig Model of Ischemic Cardiogenic Shock Treated With Veno-Arterial ECMO. Issue 2 (February 2017) - Vanhuyse, Fabrice; Ducrocq, Nicolas; Louis, Huguette; Kattani, Narimane Al; Laurent, Nicolas; Joineau-Groubatch, Frédérique; Falanga, Aude; Maureira, Juan-Pablo; Kimmoun, Antoine; Girerd, Nicolas; Tran, Nguyen; Levy, Bruno
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Cardiogenic shock (CS) patients treated with extracorporeal membrane oxygenation (ECMO) have severe cardiac failure, associated with ischemia-reperfusion. The use of moderate hypothermia during ischemia-reperfusion syndrome is supported by experimental data. We therefore studied the effects of moderate hypothermia on cardiac and vascular function in pig ischemic CS treated with veno-arterial extracorporeal membrane oxygenation (VA-ECMO). CS was induced in 12 anesthetized pigs by coronary ligation. After 1 h of CS, VA-ECMO was initiated and pigs were randomized to normothermia (38°C) or moderate hypothermia (34°C) during 8 h. Intrinsic cardiac function was measured using a left ventricular conductance catheter. At the end of the experiment, tissues were harvested for Western blotting. ECMO associated with norepinephrine infusion and volume resuscitation increased mean arterial pressure, mixed venous oxygen saturation as well as carotid, renal, and coronary blood flow without any differences between normothermia and hypothermia. Hypothermia was associated with less fluid and less norepinephrine infusion, lower lactate level, and higher urinary output. Vascular reactivity was superior in hypothermia comparatively to normothermia as expressed using norepinephrine dose-response curves. Pressure development during isovolumic contraction, left ventricular ejection fraction, and prerecruitable stroke work index were higher in the hypothermia group. There were no differences between normothermia and hypothermia with regard to carotid and mesenteric protein expression for iNOs, eNOS, and phospho AKt/AKt measured at the end of the experimentation. The incidence of surgical bleeding and coagulation disorders was the same in both groups. In conclusion, moderate and rapid hypothermia improves hemodynamics and cardiac and vascular function in a pig model of ischemic CS treated with ECMO.